Photographic Analysis of Macro- Aand Micro-Aesthetic Appearance in a Sample of Iraqi Adults With Class I Normal Occlusion - Dana R. Mohammed; Iman Al-Sheakli (College of Dentistry/ University of Baghdad, 2017)
ABSTRACT Background: Generally, the facial esthetics depends on the esthetic appearance of the maxillary anterior teeth. The purposes of this study were to analyse the macro-aesthetic appearance of the face and the micro-aesthetic appearance of the maxillary anterior teeth to establish the normative values for class I normal occlusion and to detect possible gender differences. Materials and methods: The sample consisted of 120 Iraqi adults (60 males and 60 females) aged (18-23) years. Each individual was clinically examined, then with cephalostat based head position, extraoral and intraoral photographs were taken for each subject. The facial and dental measurements were measured using AutoCad program 2014. Descriptive statistics was obtained for the measured variables for both genders and independent samples t-test was performed to evaluate the genders difference. Results and conclusions: The results showed that there is a highly significant gender difference in most of the measured variables regarding the macro-aesthetic appearance, since the males have a larger facial dimensions than females, while for the micro-aesthetic appearance, there is a non-significant gender difference in most of the measured variables, that means the proportions of maxillary anterior teeth does not affected by gender difference